2021
DOI: 10.1021/acs.jafc.1c02753
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Environmental Risk of Chlorpyrifos Application through Appropriate Agricultural Management: Evidence from Carbon-14 Tracking

Abstract: Chlorpyrifos (CPF) is one of the most critical insecticides in the world. However, many countries are gradually banning its use due to its reported hazardous impacts on humans. This study explored the possibility of reducing the environmental risk of CPF through appropriate agricultural management practices. Results showed that the environmental risk of CPF is lower under drainage conditions because there is more mineralization and less bound residues (BRs) than under submerged conditions. Bioaugmentation sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Some studies have demonstrated that the persistence of inoculum in the environment is a key factor of bioaugmentation ( Chi et al, 2013 ; Yang et al, 2021 ). Our previous study showed the inoculated exogenous degrading strain could not survive well in soil, resulting in the decrease of chlorpyrifos mineralization rate ( Jia et al, 2021a ). By qRT-PCR and 16S rRNA-amplicon sequencing, we found that the inoculated strain AT-5 survived well in the soil and remained relatively stable during the incubation period of 14 days, which ensured its remediation efficiency for atrazine-contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have demonstrated that the persistence of inoculum in the environment is a key factor of bioaugmentation ( Chi et al, 2013 ; Yang et al, 2021 ). Our previous study showed the inoculated exogenous degrading strain could not survive well in soil, resulting in the decrease of chlorpyrifos mineralization rate ( Jia et al, 2021a ). By qRT-PCR and 16S rRNA-amplicon sequencing, we found that the inoculated strain AT-5 survived well in the soil and remained relatively stable during the incubation period of 14 days, which ensured its remediation efficiency for atrazine-contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
“…By qRT-PCR and 16S rRNA-amplicon sequencing, we found that the inoculated strain AT-5 survived well in the soil and remained relatively stable during the incubation period of 14 days, which ensured its remediation efficiency for atrazine-contaminated soils. In addition, bioremediation is often subject to environmental constraints, such as soil type ( Jia et al, 2021a ). However, strain AT-5 showed good remediation effects in three different soils collected from Jining, Langfang, and Xuzhou, China ( Supplementary Figures S3 , S4 ), indicating that strain AT-5 has great potentials for the remediation of atrazine-contaminated different types of soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Degradation experiments were conducted on nine soil samples obtained from Kakira, Lugazi, and Kalangala, utilizing a slightly modified procedure based on the work of Awasthi and Prakash (1997) and Jia et al (2021). Each soil sample was divided into two groups: unsterilized and sterilized soils.…”
Section: Under Submerged Conditionsmentioning
confidence: 99%
“…By the methods outlined by Awasthi and Prakash (1997) and Jia et al (2021), three soils, namely K7, Lira, and Kitoke, were employed in this study with minor adjustments. Triplicate samples weighing 5 grams each of sterilized and unsterilized soils were carefully placed in 50 mL polycarbonate centrifuge tubes.…”
Section: Under Field Capacity Conditionsmentioning
confidence: 99%